Those Who Hear Music: Three Cases on Musical Hallucinations - Doluweera, Yasira; Suraweera, Chathurie (Case Reports in Psychiatry, 2018)
Musical hallucination carries no diagnostic significance on its own. However, it is an interesting phenomenon which can occur in various organic and psychiatric disorders. We report three patients who presented with musical hallucinations due to different aetiologies, namely, due to hearing impairment, intracerebral haemorrhage, and schizophrenia. The case series also highlights the fact that different aetiologies should be managed differently for the patients to be benefited.